2010
DOI: 10.1007/s00402-010-1216-y
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic acromioclavicular joint arthritis in arthroscopic rotator cuff tendon repair: a prospective randomized comparison study

Abstract: This study shows that distal clavicle resection combined with rotator cuff repair for asymptomatic ACJ arthritis with inferiorly directed osteophytes lower functional scores due to temporary pain in early postoperative periods, but better functional outcomes with satisfactory pain relief and no reoperation rate were observed after 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 17 publications
2
40
0
3
Order By: Relevance
“…In recent years, distal clavicle resection for AC joint arthritis has been performed arthroscopically, and it is possible to simultaneously treat rotator cuff lesions. Kim et al [35] reported good results for arthroscopic distal clavicle resection combined with rotator cuff repair. Arthroscopic distal clavicle resection is a useful method that can simultaneously treat concomitant rotator cuff lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, distal clavicle resection for AC joint arthritis has been performed arthroscopically, and it is possible to simultaneously treat rotator cuff lesions. Kim et al [35] reported good results for arthroscopic distal clavicle resection combined with rotator cuff repair. Arthroscopic distal clavicle resection is a useful method that can simultaneously treat concomitant rotator cuff lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well known that a total resection of the lateral clavicle may result in the destabilization of the whole clavicle. [19] Another study by Kim [4] showed that excision of the distal clavicle combined with rotator cuff repair for asymptomatic AC joint arthritis has lower functional scores because of temporary pain in the early postoperative period, but better functional outcomes with satisfactory pain relief and no reoperation rate were observed after 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Outlet impingement typically begins at the anteroinferior aspect of the acromion and progress medially to involve the acromioclavicular (AC) joint. [4,5] After acromioplasty, an abrupt step-off may be formed between acromion and distal end of the clavicle, which may behave like a spur. Distal clavicle coplaning was advocated in the original descriptions of arthro- plasty with and without coplaning in patients without AC arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…If nonsurgical intervention is pursued, then physical therapy or an ultrasound‐guided injection of steroid in the biceps tendon sheath is an option [50,51]. Similarly, if the acromioclavicular joint is tender, then a distal clavicle excision or acromioclavicular joint injection may be indicated [52,53].…”
Section: Discussionmentioning
confidence: 99%